An Acvr1 R206H knock-in mouse has fibrodysplasia ossificans progressiva - Chakkalakal, Salin A. (2012)
Fibrodysplasia ossificans progressiva (FOP; MIM #135100) is a debilitating genetic disorder of dysregulated cellular differentiation characterized by malformation of the great toes during embryonic skeletal development and by progressive heterotopic endochondral ossification post-natally. Patients with these classic clinical features of FOP have the identical heterozygous single nucleotide substitution (c.617G>A; R206H) in the gene encoding ACVR1/ALK2, a bone morphogenetic protein (BMP) type I receptor. Gene targeting was used to develop a knock-in mouse model for FOP (Acvr1(R206H/+)). Radiographic analysis of Acvr1(R206H/+) chimeric mice revealed that this mutation induced malformed first digits in the hind limbs and post-natal extra-skeletal bone formation, recapitulating the human disease. Histological analysis of murine lesions showed inflammatory infiltration and apoptosis of skeletal muscle followed by robust formation of heterotopic bone through an endochondral pathway, identical to that seen in patients. Progenitor cells of a Tie2+ lineage participated in each stage of endochondral osteogenesis. We further determined that both wild-type and mutant cells are present within the ectopic bone tissue, an unexpected finding that indicates that although the mutation is necessary to induce the bone formation process, the mutation is not required for progenitor cell contribution to bone and cartilage. This unique knock-in mouse model provides novel insight into the genetic regulation of heterotopic ossification and establishes the first direct in vivo evidence that the R206H mutation in ACVR1 causes FOP.